The adaptive significance of hatching synchrony of waterfowl eggs - Flint, Paul L; Lindberg, Mark S; MacCluskie, Margaret C; Sedinger, James S (Wildfowl, 2025)
We estimated the amount of incubation time that first laid Black Brent eggs received before completion of the clutch. First laid eggs received up to 48 hours of incubation before the last egg was laid in Brent clutches. Waterfowl clutches usually hatch within a period of 24 hours, suggesting that dome mechanism reduces developmental asynchrony during incubation. The combination of incubation during laying and hatch synchronization mechanisms should be adaptive because these traits reduce nest exposure, maintain egg viability, and result in an earlier hatch date, all of which increase fitness in waterfowl.